A new species of Crematogaster (Hymenoptera: Formicidae: Myrmicinae) with contrasting coloration unique to the Caribbean - Gianpiero Fiorentino; América Sánchez; Phillip Barden (Novitates Caribaea)
The cosmopolitan ant genus Crematogaster is a conspicuous lineage of myrmicine ants. Here, we describe a new species from Hispaniola, Crematogaster dorada sp. nov. C. dorada is readily diagnosable from other Caribbean ants through mesosomal thoracic sculpturing and a unique color pattern; its taxonomic affinities are consistent with other members of the Neocrema clade in the Orthocrema group, a lineage with no previous record in the Caribbean. The current diversity of Greater Antilles Crematogaster now stands at 10 species and three putative subspecies. Expanded sampling will likely yield additional species as much of the Caribbean fauna has been unrevised since the early 20th century.